Effect of L-arginine conjugated carbon nanotube (CNT) reinforced sulfonated polyether ether ketone (SPEEK) nanofilms on cell proliferation - Kaya, Hatice. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2017., 2017)
Poly ether ether ketone (PEEK) exhibits distinct properties which are favorable in designing a novel load-bearing implant for bone reconstruction. It overcomes the adverse eﬀects of metallic implants such as stress shielding, release of toxic ions and radiotherapy interference. PEEK has comparatively closer elastic modulus to that of cortical bone than metallic implants, which in turn prevents stress shielding and subsequent bone resorption. Furthermore, elastic modulus of PEEK is tunable by incorporation of additives. However, hydrophobic bioinert surface of PEEK which are not favorable for cell adhesion brings about some limitations in its application due to ineﬃcient osseointegration. Furthermore, although the addition of ﬁllers promote the mechanical attributes, PEEK nanocomposite might be still insuﬃcient regarding inducement of bioactivity. Many studies show that presence of L-arginine (L-Arg) assists cell attachment and proliferation. In this thesis, functionalized multi-walled carbon nanotubes (f-MWCNT) reinforced sulphonated poly ether ether ketone (SPEEK) was fabricated by solvent casting. Previously, PEEK was dissolved in high concentric sulfuricacid(H2SO4)togainSPEEKandMWCNTwasoxidizedwithmixingofsulfuricacid (H2SO4, 98%) and nitric acid (HNO3, 65%) to obtain carboxyl groups on the sidewall and ends of MWCNT. The surface of the obtained nanoﬁlms were covalently conjugated with L-arginine. The samples were characterized with Proton Nuclear Magnetic Resonance Spectroscopy (H-NMR), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Photoelectron Spectroscopy (XPS), Water Contact Angle (WCA) measurement, Atomic Force Microscope (AFM) and Dynamic Mechanical Analysis (DMA).Finally, impactofCNTandL-argexistenceoncellularresponsewasanalyzedusinghumanfetal osteoblast (hFOB) via Alamar blue test. The chemical characterization of surface with FTIR and H-NMR, functional sulfur and carboxyl groups formed were conﬁrmed. Immobilization of L-Arg was conﬁrmed via XPS showing the Nitrogen (N) atom presence and chemical state of N atom. The mechanical strength of nanoﬁlms were improved which was proven by DMA. Cell viability was observed the highest for L-arg grafted nanoﬁlm. In conclusion, this study indicates that arginine modiﬁed CNT/PEEK ﬁlms are promising candidates for femoral replacement applications.
Keywords: Carbon.; Polyethers.; Nanotubes.